Export Performance and Trade Competitiveness of India’s Frozen Shrimps: A Temporal Analysis - Santhosha, K.M,; , A.D. Naik; , Ganeshagouda I. Patil; , C.G. Yadava; Srinivasulu G. B.,; Raghavendra, (Archives of Current Research International, 2024)
Shrimps are crucial aquaculture species that contribute significantly to the economy, including farm income, employment, and export earnings. India, the world's second-largest producer of aquaculture products, has yet to exploit its potential in aquaculture exports fully. The export of frozen shrimp has been increasing due to large consumption by importing countries and sufficient exportable surplus. This study analysed the export competitiveness and direction of exports to various markets using the Nominal Protection Coefficient (NPC) and Markov Chain Analysis. The analysis revealed that all countries were competitive in exporting frozen shrimp from India, with the United States, Southeast Asia, and China being the most loyal importers. The study projected shrimp export for the next five years, with the USA being the major destination in the future. However, Japan's share in the future will decrease due to importing frozen shrimp from Indonesia and Vietnam. Policymakers are now attempting to regain trade by adopting suitable policy measures. The study highlights the importance of evaluating export competitiveness and market direction in the era of globalisation and the need for effective trade promotion and price competitiveness.